Effectiveness of Cognitive Restructuring Technique in the Reduction of Test Anxiety among Senior Secondary School Students in Benin Metropolis of Edo State, Nigeria (Journal of Guidance and Counselling Studies, 2021)
This study examined the effectiveness of Cognitive Restructuring Technique in the reduction of test anxiety among secondary school students in Benin metropolis of Edo state. One Hypothesis was formulated by the researcher which was tested at 0.05 level of significant. The pre-test post-test, control group quasi experimental design was used for the study. The population of this study consists of all the public senior secondary schools students in SSII in Benin metropolis, Edo State. The population of this category of students for the year 2018/2019 academic session is 13,889. Of which 6,032 are males and 7,857 are females. Two senior secondary schools from two Local Government Areas in Benin metropolis Edo State were used for the study. The two local government areas were purposively selected for the study. One senior secondary school was also purposively selected from each of the two Local Government Areas. The reason for the purposive selection was because quasi experimental research design does not give room for randomization. The total number of SSII students in the two senior secondary schools that were selected for the study was 418. One intact class that has the highest population of students in each school was selected for the study giving a total sample of 212 students out of which 95 were males and 117 were females. The students were assigned to one treatment group and a placebo control group. The instrument used for collection of data was the Test Anxiety Inventory (TAI). Mean and standard deviations analysis were used to analyze the demographic variables of the participants while, t-test and Analysis of Covariance (ANCOVA) were used to test the hypotheses. The study revealed that Cognitive Restructuring Technique is effective in the reduction of test anxiety scores among secondary school students in Benin metropolis of Edo state. It was recommended that the school counsellors can use Cognitive restructuring technique to manage test anxiety of (among) students.